TATA KELOLA REKAM MEDIS ELEKTRONIK BERBASIS TEKNOLOGI INFORMASI PADA PENANGANAN RESUME MEDIS PASIEN DENGAN METODE AGILE - Mita Mutia; Nita Nurdianti; Falaah Abdussalaam; Yuyun Yunengsih (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This study contains a medical resume management system using a programming language using Microsoft Visual Studio 2012 at Pusat Mata Nasional Rumah Sakit Mata Cicendo. The research method used by the author is a qualitative research method which is based on the philosophy of postpositivism, observation, and software development methods using the Agile Method, a software methodology based on the work process with stages starting from requirements, design, development, testing, deployment. The problem found in this research is to first summarize and write the manual of the existing application onto paper after that it is typed in Microsoft Word, then printed, so it is less efficient. Therefore, to overcome these problems, the authors created an integrated medical resume governance system to facilitate the process of creating an effective and efficient medical resume, including the registration process, patient data, doctor data, polyclinic data, medical information document retrieval data, reports. retrieval, and medical resume reports. With a medical resume management system, the process of making medical resume submissions will be faster and on time.